Geologia e geoquímica do batólito granitoide Itaoca, sul do estado de São Paulo - Zenero, Jonas Menezes [UNESP] (2020)
The Itaoca Granite is an intrusive circular batholith of 200 km2, located between the state of São Paulo and Paraná, more specifically on the center of Apiaí topographic sheet, in a 1:50,000 scale. It has an approximate age of 623 Ma, associated with the neoproterozoic evolution of the Central Mantiqueira Province. Its enclosing rocks of metavulcan-sedimentary composition make up the Lajeado Group of the Açungui Supergroup and present, in the surroundings of the batolith, a typical contact metamorphic mineralogy, with facies that vary from the epidote hornfels facies on the edges to the pyroxene hornfels, in the roof pendants. Using textural, structural, coloring and compositional aspects of the rock, the massif was further divided into two units, called Itaoca and Ribeira, subdivided into 6 facies, in addition to an association of undifferentiated facies. Petrographically, its rocks consist basically of hornblende-biotite-quartz monzonites to holo-leucocratic monzogranites. They have porphyritic texture, medium to coarse, isotropic to suborientated granulation. The Itaoca unit consists of less evolved rocks (quartz monzonites), possibly a primary magmatic pulse against the Ribeira Unit. Geochemically, the granitoid rocks are a cordilherian type I alkaline peraluminous calcium granite, sin a tardi collisional of magmatic arc environment by the fusion of the lower crust. Geological evolution is determined by the neoproterozoic tectonic-metamorphic arrangement, which is defined by three deformational phases. The two initial events are related to a tangential tectonic, linked to the collisional phase and consequent thickening of crustal masses followed by placement and partial deformation at the edges of the Itaoca batolith. The posterior deformation is marked by a transcurrent/transpressive tectonic in which occurs associated with late magmatic ascension and the deformed portion of the granite, classified within the association of undifferentiated facies. The progressive regional metamorphism is of the Barrovian type, with rocks in high green schist facies, with local occurrences of contact and dynamic metamorphism that have a retrometamorphic nature.